A monoamine oxidase-A inhibitor phthalocyanine conjugate for targeted photodynamic therapy and inhibition of prostate cancer metastasis in vitro. (November 2022) - Zhao, Xuan; Wang, Qilu; Jia, Xiao; Xue, Jinping; Chen, Juanjuan
Abstract: Photodynamic therapy (PDT), as an alternative non-invasive clinical treatment modality, has been extensively employed for various anticancer applications in preclinical and clinical trials. However, there is hardly any PDT research based on invasive or metastatic tumors. But it can't be ignored that cancer metastases are responsible for 90% of all cancer-related death. Among these metastatic cancers, prostate cancer (PCa) is regarded as one of the leading causes of cancer related deaths amongst male patients due to its high metastasis and high fatality rate. At present, it remains a great challenge to apply traditional PDT technology for inhibiting prostate cancer metastasis. In this work, we successfully designed and synthesized a novel MAO-A targeted photosensitizer Pc-MLB for targeted photodynamic treatment of prostate cancer and inhibiting its metastasis in vitro. In vitro experiments demonstrate that Pc-MLB shows high target affinity and specificity towards prostate cancer cells and remarkable photodynamic anticancer activity compared with the control. More significantly, the migration and invasion assays show that Pc-MLB exhibits the ability to inhibit the migration and metastasis of prostate cancer cells to some extent. Graphical abstract: Image 1 Highlights: A novel MAO-A targeted photosensitizer Pc-MLB is rationally designed and successfully synthesized. Pc-MLB shows prominent tumor targeting selectivity and affinity. Pc-MLB exhibits remarkable photodynamic anticancer activity. Pc-MLB has ability to inhibit the migration and metastasis of prostate cancer cells to some extent.